NGC 6240 supermassive black hole binary dynamical evolution based on Chandra data - Sobolenko, Margaryta; Kompaniiets, O; Berczik, Peter; Marchenko, V; Vasylenko, A; Fedorova, E; Shukirgaliyev, B (Monthly notices of the Royal Astronomical Society, 2022)
The main idea of our research is to estimate the physical coalescence time of the double supermassive black hole (SMBH) system in the centre of NGC 6240 based on the X-ray observations from the Chandra space observatory. The spectra of the northern and southern nuclei were fitted by spectral models from Sherpa and both presented the narrow component of the Fe Kα emission line. It enabled us to apply the spectral model to these lines and to find relative offset ≈0.02 keV. The enclosed dynamical mass of the central region of NGC 6240 with radius 1 kpc was estimated $≈ 2.04× 10^{11} \rm \,\, M_{\odot }$. These data allowed us to carry on the high-resolution direct N-body simulations with Newtonian and post-Newtonian (up to $2.5\mathcal {PN}$ correction) dynamics for this particular double SMBH system. As a result, from our numerical models, we approximated the central SMBH binary merging time for the different binary eccentricities. In our numerical parameters range, the upper limit for the merging time, even for the very small eccentricities, is still below ≈70 Myr. Gravitational waveforms and amplitude-frequency pictures from such events can be detected using pulsar timing array projects at the last merging phase.
Published: 06 September 2022
Gesehen am 18.01.2023